Engineered multifunctional nanocarriers for controlled drug delivery in tumor immunotherapy - Katopodi, Theodora; Petanidis, Savvas; Tsavlis, Drosos; Anestakis, Doxakis; Charalampidis, Charalampos; Chatziprodromidou, Ioanna; Eskitzis, Panagiotis; Zarogoulidis, Paul; Kosmidis, Christoforos; Matthaios, Dimitris; Porpodis, Konstantinos (Frontiers in Oncology, 2022)
The appearance of chemoresistance in cancer is a major issue. The main barriers to conventional tumor chemotherapy are undesirable toxic effects and multidrug resistance. Cancer nanotherapeutics were developed to get around the drawbacks of conventional chemotherapy. Through clinical evaluation of thoughtfully developed nano delivery systems, cancer nanotherapeutics have recently offered unmatched potential to comprehend and combat drug resistance and toxicity. In different design approaches, including passive targeting, active targeting, nanomedicine, and multimodal nanomedicine combination therapy, were successful in treating cancer in this situation. Even though cancer nanotherapy has achieved considerable technological development, tumor biology complexity and heterogeneity and a lack of full knowledge of nano-bio interactions remain important hurdles to future clinical translation and commercialization. The recent developments and advancements in cancer nanotherapeutics utilizing a wide variety of nanomaterial-based platforms to overcome cancer treatment resistance are covered in this article. Additionally, an evaluation of different nanotherapeutics-based approaches to cancer treatment, such as tumor microenvironment targeted techniques sophisticated delivery methods for the precise targeting of cancer stem cells, as well as an update on clinical studies are discussed. Lastly, the potential for cancer nanotherapeutics to overcome tumor relapse and the therapeutic effects and targeted efficacies of modern nanosystems are analyzed.